Bio-based materials and biotechnologies for eco-efficient construction - Pacheco-Torgal, F. (2020)
Over more recent years, society has witnessed an increasing demand for natural, bio or biotech-based products for use in a broad range of industrial applications, mainly because of environmental issues, waste disposal problems, and the depletion of non-renewable resources. In 2002 the EU launched its Strategy on Biotechnology. Then in 2012 The European Commission created the world?s first bio-economy strategy and action plan. With a turnover value of ?2.3 trillion and accounting for 8.2% of the EU?s workforce the bio-economy is now a central element for the functioning and success of the EU economy. According to their new strategy the bio-economy will provide support for the modernisation and strengthening of the EU industrial base through the creation of new value chains and greener more cost-effective industrial processes. The demand for bio-based products is increasing worldwide and EU demand alone is estimated to grow to 50 billion of market value by 2030. It is also anticipated that bio-based industries could help create one million new jobs by 2030. Under the responsibility of the European Commission they recently stressed that the EU must accelerate the pace in switching industry production to; renewable, climate-neutral, bio-based resources having disclosed a ?100 million Circular Bioeconomy Thematic Investment Platform for risk-sharing with developers of bio-based solutions. Unfortunately, a disconnect continues to exist between the field of civil engineering and those working in biotech research that is mostly conducted in biology and biotechnology departments. The fact that biologists and engineers both typically speak a very different language, creates communication challenges which further aggravates this divide. A serious problem that this book will tackle will be helping future practitioners in the construction industry to understand the language of their fellow colleagues working in biology in order to enhance future collaboration between the two areas.